2017
DOI: 10.20344/amp.8217
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Real-Life Utilization of Ranibizumab in Patients with Wet Age-Related Macular Degeneration from Portugal

Abstract: These findings indicate that as-needed treatment resulted in under-dosing in a real-life setting in Portugal. Such limitations may also be related to increasing numbers of patients, resulting in clinic saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
1
9
0
Order By: Relevance
“… 6 , 8 , 9 , 12 However, this number was reported as low as 3-4 in most of the real-world practice studies. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 In addition, 12-13 visits are necessary in an ideal PRN treatment follow-up protocol. 6 , 7 The mean visit number was 6.9 in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 6 , 8 , 9 , 12 However, this number was reported as low as 3-4 in most of the real-world practice studies. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 In addition, 12-13 visits are necessary in an ideal PRN treatment follow-up protocol. 6 , 7 The mean visit number was 6.9 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous real-world studies the mean visit number was found to be between 6 and 12. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations